Carbon nitride-based composite piezoelectric-photocatalytic material and preparation method and application thereof
Patent Information
- Application Number
- CN202610400722.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-30
- Publication Date
- 2026-10-13
AI Technical Summary
现有技术中的复合材料降解有机污染物的效率仍有待提高,并且现有技术中复合材料降解有机污染物的同时不能产生氢气
[0021]有益效果:与现有技术相比,本发明具有如下显著优点:(1)本发明通过将氮化碳纳米片和花状二硫化钼结合,两者接触面在仅光激发下形成I型异质结,并且在压电条-光件下转化为S型异质结,具有高效降解有机污染物的能力,并且在降解有机污染物的同时协同产氢;(2)二硫化钼与氮化碳的质量比为1:5形成复合压电-光催化材料,对四环素的60min降解率高达95%,实现了“1+1>2”的显著协同效果;(3)本发明的催化剂的制备方法简单,易于工业化;(4)本发明的复合压电-光催化材料不仅能高效降解四环素,还可同时实现氢气的生成,体现了“污染物降解-能源回收”一体化的双重功能,为废水资源化利用提供了新材料途径;(5)本发明的复合压电-光催化材料具有良好的稳定性与适应性,在多种实际水体连续流实验中均保持高效性能,展现出突出的实际应用潜力。
Smart Images

Figure CN122895018A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of piezoelectric-photocatalysis technology, and specifically relates to a carbon nitride-based composite piezoelectric-photocatalytic material, its preparation method, and its application. Background Technology
[0002] With the rapid development of the pharmaceutical industry, a large amount of antibiotics enters the aquatic environment through pharmaceutical wastewater and medical discharges. Among them, tetracycline antibiotics have attracted much attention due to their recalcitrant degradation and ecotoxicity. Advanced oxidation technologies are effective means to treat such recalcitrant organic pollutants, and photocatalysis technology has been widely studied due to its advantages such as direct utilization of solar energy and mild reaction conditions. However, traditional semiconductor photocatalysts generally suffer from bottlenecks such as low visible light utilization and rapid recombination of photogenerated electron-hole pairs, resulting in degradation efficiency that cannot meet practical needs.
[0003] In recent years, piezoelectric-photocatalysis, as an emerging synergistic catalytic strategy, has provided a new approach to solving the aforementioned bottlenecks. This technology introduces mechanical vibrational energy to generate an internal polarized electric field in the piezoelectric catalyst. This electric field serves as a powerful driving force, effectively promoting the separation and directional migration of photogenerated carriers, thereby significantly improving the quantum efficiency of the photocatalytic reaction. This means that the technology can synergistically utilize the widely available mechanical energy and solar energy in the environment to achieve a catalytic synergy of "1+1>2". The core of achieving efficient piezoelectric-photocatalysis lies in the design of the catalyst. Ideal materials need to possess both good piezoelectric response to generate a strong polarized electric field and excellent semiconductor properties to achieve efficient light absorption and charge generation. However, a single material often cannot simultaneously meet both requirements. For example, classic piezoelectric ceramic materials (such as BaTiO3) have strong piezoelectricity but a wide band gap, and hardly absorb visible light; while common photocatalysts (such as TiO2) have good photoresponse, but their piezoelectric effect is weak or even nonexistent. The efficiency of composite materials in degrading organic pollutants in existing technologies still needs to be improved, and existing composite materials cannot generate hydrogen gas while degrading organic pollutants. Summary of the Invention
[0004] Objectives of the Invention: The first objective of this invention is to provide a carbon nitride-based composite piezoelectric-photocatalyst material that improves the degradation efficiency of organic pollutants and simultaneously promotes hydrogen production during the degradation process; the second objective of this invention is to provide a method for preparing the carbon nitride-based composite piezoelectric-photocatalyst material; and the third objective of this invention is to provide applications of the carbon nitride-based composite piezoelectric-photocatalyst material.
[0005] Technical solution: The carbon nitride-based composite piezoelectric-photocatalytic material of the present invention is formed by depositing flower-shaped molybdenum disulfide nanoparticles (MoS2) on the surface of carbon nitride nanosheets (ECN), wherein the molybdenum disulfide is 2H molybdenum disulfide; the contact surface between the molybdenum disulfide and carbon nitride forms a type I heterojunction under photoexcitation only, and transforms into an S-type heterojunction under piezoelectric-photoelectric conditions.
[0006] Preferably, the mass ratio of molybdenum disulfide to carbon nitride is 1:2 to 1:10. If the content of the piezoelectric component molybdenum disulfide is too low, the generated piezoelectric polarization field will be insufficient to fully drive carrier separation; if the content of the photocatalytic component carbon nitride is too low, the light absorption capacity will be insufficient, and the catalytic activity will be insufficient.
[0007] Preferably, the thickness of the carbon nitride nanosheets is 4~72 nm.
[0008] Preferably, the flower-shaped molybdenum disulfide nanoparticles have a particle size of 200~300 nm.
[0009] The preparation method of the carbon nitride-based composite piezoelectric-photocatalytic material of the present invention includes the following steps: dispersing carbon nitride nanosheets and flower-shaped molybdenum disulfide nanoparticles in a solvent, ultrasonically mixing them evenly, drying them, and finally calcining them to obtain the carbon nitride-based composite piezoelectric-photocatalytic material.
[0010] The purpose of uniform mixing is to ensure that the molybdenum disulfide particles do not stack up, but can be uniformly attached to the surface of carbon nitride nanosheets and form a heterojunction interface; the purpose of calcination is to transform the physical contact that originally relied on van der Waals forces into stronger chemical bonds through thermal drive and to remove any surfactants or solvent molecules that may remain in the preparation process.
[0011] Preferably, the calcination conditions are calcination at 290~300℃ for 1~1.5 hours under an inert gas atmosphere.
[0012] Preferably, the solvent is ethanol.
[0013] Preferably, the carbon nitride nanosheets are prepared by: heating melamine to 550°C in air atmosphere and calcining for 4 hours to obtain bulk carbon nitride; then calcining and exfoliating it at 500°C for 2 hours to obtain carbon nitride nanosheets (ECN).
[0014] Preparation method of flower-shaped molybdenum disulfide nanoparticles: 41.13 mg of sodium molybdate dihydrate (Na2MoO4·2H2O) and 66.58 mg of N-acetyl-L-cysteine (NAC) were dissolved in 40 mL of ultrapure water in an ice bath. Then, 25.88 mg of thiourea (CH4N2S) was added to the above solution, and the mixture was stirred for 1 h. The mixed solution was transferred to a 50 mL polytetrafluoroethylene-lined container, placed in an autoclave, and kept in an oven at 200 °C for 24 h. After the reaction was completed, the filtered black precipitate was washed with deionized water and ethanol, and dried overnight in an oven at 60 °C to obtain 2HMoS2.
[0015] The present invention relates to the application of the carbon nitride-based composite piezoelectric-photocatalytic material in the degradation of organic pollutants and / or the generation of hydrogen.
[0016] Preferably, the application is carried out under the synergistic conditions of mechanical vibration and light irradiation; the mechanical vibration is provided by ultrasound with a frequency of 20~50 kHz; and the light irradiation is full spectrum.
[0017] Preferably, the organic pollutant is tetracycline.
[0018] Invention Mechanism:
[0019] Molybdenum disulfide (MoS2) exhibits excellent piezoelectric properties due to its non-centrosymmetric crystal structure, generating a significant piezoelectric potential under mechanical stress, making it a highly promising piezoelectric component. Graphitic carbon nitride (g-C3N4), as a non-metallic polymer semiconductor, possesses a suitable visible light absorption bandgap and good chemical stability, making it a classic photocatalytic material.
[0020] This invention constructs a heterojunction by combining ECN and MoS2. For example... Figure 1 As shown, DFT calculations indicate that the work function of ECN (4.46 eV) is lower than that of MoS2 (5.05 eV). After they come into contact, electrons spontaneously flow from ECN to MoS2 until the Fermi level reaches equilibrium, causing the ECN band to bend upwards and the MoS2 band to bend downwards, forming a built-in electric field from ECN to MoS2. Under a single optical field, this band arrangement constitutes a type I heterojunction: photogenerated electrons are enriched in the more reducing ECN conduction band, while holes are transferred to the MoS2 valence band, achieving a certain degree of charge separation. Unexpectedly, when a piezoelectric field (ultrasound) is applied simultaneously, the piezoelectric polarization field generated by MoS2 couples with the built-in electric field of the heterojunction, inducing further tilting and bending of the interface bands, transforming the charge transport path into an S-type heterojunction mechanism. EPR experiments ( Figure 7 This confirms that under piezoelectric photon conditions, superoxide radicals (·O2) -Both the I-type and S-type signals were significantly enhanced, indicating that electrons and holes are enriched in the ECN conduction band, which has stronger reducing power, and the MoS2 valence band, which has stronger oxidizing power, respectively. This transition from the I-type to the S-type enables the effective separation and enrichment of strong reducing electrons and strong oxidizing holes, thereby efficiently driving the tetracycline degradation reaction and achieving a deep synergy between the piezoelectric effect and the photocatalytic effect.
[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The present invention combines carbon nitride nanosheets and flower-shaped molybdenum disulfide. The contact surface of the two forms a type I heterojunction under photoexcitation only, and transforms into a type S heterojunction under piezoelectric strip-light element. It has the ability to efficiently degrade organic pollutants and synergistically produce hydrogen while degrading organic pollutants; (2) The mass ratio of molybdenum disulfide to carbon nitride is 1:5 to form a composite piezoelectric-photocatalytic material. The degradation rate of tetracycline in 60 min is as high as 95%, realizing the significant synergistic effect of "1+1>2"; (3) The preparation method of the catalyst of the present invention is simple and easy to industrialize; (4) The composite piezoelectric-photocatalytic material of the present invention can not only efficiently degrade tetracycline, but also generate hydrogen at the same time, reflecting the dual function of "pollutant degradation-energy recovery" integration, and providing a new material approach for wastewater resource utilization; (5) The composite piezoelectric-photocatalytic material of the present invention has good stability and adaptability. It maintains high efficiency in various actual water continuous flow experiments and shows outstanding practical application potential. Attached Figure Description
[0022] Figure 1 This is a mechanism diagram of the carbon nitride-based composite piezoelectric-photocatalyst material of the present invention under light and piezoelectric light conditions;
[0023] Figure 2 This is a thickness characterization diagram of ECN;
[0024] Figure 3 X-ray diffraction (XRD) patterns of the catalytic materials prepared in Examples 1-3 and Comparative Examples 1-2;
[0025] Figure 4 Here is a scanning electron microscope (SEM) image of the catalytic material prepared in Example 2;
[0026] Figure 5 High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) image of the catalytic material prepared in Example 2;
[0027] Figure 6 The butterfly curve and phase hysteresis plot of the catalytic material prepared in Example 2;
[0028] Figure 7The image shows the results of treating the superoxide radical and hydroxyl groups of the catalytic material prepared in Example 2 under piezoelectric, light, and piezoelectric light conditions for 10 min.
[0029] Figure 8 A comparison of the first-order kinetic rate constants of TC degradation under different conditions for the catalytic materials prepared in Examples 1-3 and Comparative Examples 1-2;
[0030] Figure 9 The images show the XRD patterns of ECN before and after the piezoelectric photocatalytic degradation of TC by the catalyst material prepared in Example 2.
[0031] Figure 10 The diagram shows the hydrogen production process and the TC degradation process of the catalyst material prepared in Example 2, which simultaneously produces hydrogen and degrades TC.
[0032] Figure 11 A comparison of the first-order kinetic rate constants of TC degradation in different real water bodies during continuous flow experiments using the catalytic material prepared in Example 2;
[0033] Figure 12 The stability test diagram of the catalytic material prepared in Example 2 for the degradation of TC under piezoelectric light conditions is shown. Detailed Implementation
[0034] The technical solution of the present invention will be further described below with reference to the embodiments.
[0035] Example 1
[0036] The carbon nitride-based composite piezoelectric-photocatalytic material of the present invention is prepared by the following steps:
[0037] (1) Preparation of ECN
[0038] First, bulk graphitic carbon nitride (BCN) was prepared via direct thermal condensation of melamine. Specifically, 8 g of melamine was placed in a covered alumina crucible and heated to 550 °C at a rate of 5 °C per minute in air, and maintained at 550 °C for 4 hours. The resulting yellow bulk graphitic carbon nitride was then ground into powder. Next, carbon nitride nanosheets (ECN) were prepared via a second calcination of the bulk graphitic carbon nitride (BCN). 0.5 g of BCN was placed in an uncovered alumina crucible and heated to 500 °C at a rate of 5 °C per minute in air, and maintained at this temperature for 2 hours.
[0039] (2) Preparation of MoS2
[0040] 41.13 mg of sodium molybdate dihydrate (Na₂MoO₄·2H₂O) and 66.58 mg of N-acetyl-L-cysteine (NAC) were dissolved in 40 mL of ultrapure water in an ice bath. Then, 25.88 mg of thiourea (CH₄N₂S) was added to the solution, and the mixture was stirred for 1 h. The mixture was transferred to a 50 mL polytetrafluoroethylene-lined container, placed in an autoclave, and kept in an oven at 200 °C for 24 h. After the reaction was complete, the filtered black precipitate was washed with deionized water and ethanol, and dried overnight in an oven at 60 °C to obtain 2HMoS₂.
[0041] (3) Preparation of MoS2 / ECN
[0042] 20 mg of synthesized ECN powder and 10 mg of MoS2 powder were dispersed in 10 mL of anhydrous ethanol and ultrasonically vibrated for 1 h, followed by vigorous stirring for 10 h. After filtration, the sample was dried overnight in a vacuum oven at 60 ℃. The dried sample was then ground and placed in a tube furnace and heated under a flow of N2 at 300 ℃ for 1 h to enhance the interaction between the MoS2 nanostructure and the g-C3N4 matrix, thus obtaining a MoS2:ECN=1:2 (ME-2) catalytic material.
[0043] Example 2
[0044] Based on Example 1, the dosage of ECN and MoS2 in the third step was changed to 50 mg and 10 mg, respectively, to obtain a MoS2:ECN=1:5 (ME-5) catalyst.
[0045] Example 3
[0046] Based on Example 1, the dosage of ECN and MoS2 in the third step was changed to 100 mg and 10 mg, respectively, to obtain a MoS2:ECN=1:10 (ME-10) catalyst.
[0047] Comparative Example 1
[0048] Based on Example 1, steps (2) and (3) are omitted to obtain the ECN catalyst.
[0049] Comparative Example 2
[0050] Based on Example 1, steps (1) and (3) are omitted to obtain the MoS2 catalyst.
[0051] Structural characterization
[0052] The thickness of the ECN prepared in step (1) of Example 1 was characterized, and the results are as follows: Figure 2As shown, AFM characterization revealed that the carbon nitride nanosheets in this sample exhibited a wide thickness distribution ranging from 5 to 72 nm, indicating the simultaneous presence of both few-layer and multi-layer structures. This thickness variation helps expose more active sites and forms abundant heterojunction interfaces during recombination, thereby synergistically enhancing piezoelectric-photocatalytic performance.
[0053] The catalytic materials of Examples 1-3 and Comparative Examples 1-2 were characterized by X-ray diffraction (XRD), such as... Figure 3 As shown. (Through) Figure 3 It can be seen that the XRD pattern of ECN follows a similar pattern to that of pure g-C3N4, with two distinct diffraction peaks at 13.2° and 27.7°, representing the in-plane stacking (100) of tris-s-triazine units and the interlayer stacking (002) of conjugated double bonds in graphite, respectively. For pure MoS2, all diffraction peaks conform to the typical hexagonal 2H MoS2 structure. For the composites of different proportions in Examples 1-3, the higher the proportion of MoS2 added, the weaker the intensity of the two peaks of g-C3N4, indicating a reduction in thickness and size, which also reasonably confirms the existence of two phases.
[0054] The catalytic material prepared in Example 2 was characterized by scanning electron microscopy (SEM) and HAADF-STEM, and the results are as follows: Figures 4-5 As shown. Through SEM ( Figure 4 It can be seen that MoS2 nanoflowers are incorporated into and coated within ECN nanosheets, with the three-dimensional MoS2 nanoflowers in close contact with the two-dimensional ECN nanosheets. This can be further demonstrated by HAADF-STEM. Figure 5 The presence of the four main elements (C, N, Mo and S) was confirmed, and they were evenly distributed and closely connected, further indicating that flower-like MoS2 was densely deposited on the g-C3N4 surface.
[0055] Performance Characterization
[0056] 1. Piezoelectric performance testing
[0057] The piezoelectric properties of the catalytic material prepared in Example 2 were evaluated using piezoelectric microscopy (PFM), and the results are as follows: Figure 6 The piezoelectric coefficient d is calculated using the butterfly curve shown. 33 72 pm·V -1 Furthermore, the phase hysteresis curve of the material exhibits a near 180° phase reversal in the voltage range of -10 V and +10 V, indicating the presence of 180° piezoelectric domains. Figure 6 These results demonstrate that ME-5 possesses excellent piezoelectric properties.
[0058] 2. An EPR experiment was conducted on the catalyst material of Example 2.
[0059] Experimental Methods: The instrument used was a Bruker A300 (Germany). The EPR signal was captured by the spin trapping of the reagents 5,5-dimethyl-1-pyrrolidone-N-oxide (DMPO), 2,2,6,6-tetramethylpiperidine-1-oxygen radical (TEMPO), and 2,2,6,6-tetramethyl-4-piperidinol (TEMP). The experimental procedure typically involved several steps: the prepared sample was dissolved in methanol solution according to the specified ratio, and then DMPO (0.5 M) was added to the solution as ·O2. - The capture agent can be either dissolved in ultrapure water according to a certain ratio, or TEMPO (0.5 M) can be added to the solution as h + The trapping agent was used. These steps ensured that the captured free radicals could react with the reagents and form stable complexes for further spectral analysis. A 300W xenon lamp was used as the light source, and a 120W, 40 kHz ultrasonic cleaner was used for mechanical force. Samples were irradiated separately or simultaneously for 10 minutes. After the reaction, the mixed solution was aspirated through a capillary tube and carefully inserted into the sample chamber of the EPR spectrometer for testing. The central field was set to 3500 G, and the scan width was 100 G. The results are as follows: Figure 7 As shown.
[0060] Depend on Figure 7 Therefore, 7a (superoxide radical·O2) - The signal intensity of 7b (hydroxyl radical ·OH) directly reflects the strength of the material's conduction band electron reduction capability. The strongest signal is observed under piezoelectric light, indicating that the piezoelectric field effectively drives the migration of photogenerated electrons to the conduction band of the ECN. Simultaneously, the piezoelectric field may lower the surface barrier through band bending, further promoting the reaction between electrons and surface-adsorbed oxygen molecules. The signal intensity of 7b (hydroxyl radical ·OH) reflects the oxidation capability of holes. The significant signal under piezoelectric light proves that holes are effectively enriched in the valence band of MoS2. Notably, ·OH is usually generated by the reaction of holes with surface-adsorbed water or hydroxide ions; its enhanced signal not only verifies the participation of holes but also indirectly confirms that the piezoelectric field inhibits bulk electron-hole recombination. The EPR signal intensity of superoxide radicals and hydroxyl radicals under piezoelectric light conditions is much higher than that of ultrasound and light alone, further demonstrating the role of the piezoelectric effect in assisted photocatalysis. The material's own piezoelectric field not only directly drives the dynamic movement of free charges but also causes band bending, thereby promoting charge separation and transfer.
[0061] 3. Testing the degradation performance of catalytic materials for tetracycline
[0062] The catalysts prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to piezoelectric, light, and piezoelectric-light conditions to degrade TC. The degradation experiments included the following specific steps:
[0063] (1) Add 5 mg of catalyst and 50 mL of 0.1 g / L TC solution to a 250 mL beaker and allow it to adsorb statically for 30 min in the dark.
[0064] (2) Place the beaker in the piezoelectric photocatalytic device and expose it to light (300 W, 200 mW / cm²). 2 The catalytic activity of the samples for TC degradation was investigated under ultrasound (40 kHz, 120 W) and simultaneous light and ultrasound conditions. 0.7 mL of solution was collected at 0 min, 2 min, 5 min, 10 min, 20 min, 30 min, and 60 min and filtered through a 0.22 μm filter to remove residual catalyst particles.
[0065] (3) Subsequently, the absorbance of the TC solution was measured at a wavelength of 357 nm using a UV-Vis spectrophotometer (UV723S, APL Instruments, China) to evaluate the degradation efficiency of the catalyst on the TC solution under different conditions. The results are as follows: Figure 8 As shown in Table 1.
[0066] Table 1. First-order apparent rate constants k of the catalysts in Examples 1-3 and Comparative Examples 1-2
[0067]
[0068] Depend on Figure 8 It was found that under ultrasonic (piezoelectric) conditions, the first-order apparent rate constant k of the catalytic materials in Examples 1-3 was lower than that of MoS2, but higher than that of ECN. This is attributed to the intrinsic piezoelectric activity of MoS2, whose piezoelectric field can drive the separation of its own charge carriers. The piezoelectric catalytic activity of Examples 1-3 was between that of MoS2 and ECN, indicating that the piezoelectric response of the composite material was mainly contributed by MoS2. Under light irradiation conditions, the first-order apparent rate constant k of the catalytic materials in Examples 1-3 was higher than that of ECN and MoS2, indicating that the heterojunction formed by ECN and MoS2 effectively promoted the separation of photogenerated electron-hole pairs, thereby improving the photocatalytic efficiency. Under light-ultrasonic conditions, the degradation rate of all examples was significantly improved. In Examples 1-3, k showed a trend of first increasing and then decreasing with the increase of ECN content. The ME-5 catalyst showed the best synergistic effect and the highest efficiency (first-order apparent rate constant k = 0.050 min). -1 The efficiency of the two catalysts was 1.81 times and 19.11 times that of photocatalysis and piezoelectric catalysis, respectively.
[0069] XRD analysis of the catalyst obtained in Example 2 after undergoing piezoelectric-photocatalytic reaction yielded the following results: Figure 9 As shown, no impurities or additional crystalline phases were found, further verifying its recyclability and stability.
[0070] 4. Performance test of catalytic material for simultaneous hydrogen production from tetracycline degradation
[0071] The catalytic material of Example 2 was tested for piezoelectric-photocatalytic synergistic hydrogen production using tetracycline as a sacrificial agent.
[0072] Test method: Add 36 mL of water, 4 mL of 0.1 g / L levofloxacin solution, and 10 mg of catalyst to the reactor. Mount the reactor on a piezoelectric-photocatalytic device and evacuate for 20 min. Then purge the entire reaction apparatus three times with Ar gas to remove air and prevent interference. Turn on the magnetic stirrer, xenon lamp, and gas chromatograph. Results are as follows: Figure 10 As shown.
[0073] Depend on Figure 10 It was found that approximately 1.5786 mmol / g of hydrogen was produced within 4 hours, and the TC degradation efficiency within 4 hours was 59.79%. Hydrogen production was stably and simultaneously achieved while degrading pollutants. In this process, tetracycline acted as a sacrificial agent, effectively promoting carrier separation through its own oxidative decomposition, thereby improving hydrogen production efficiency. This indicates that the composite material of the present invention has the potential for hydrogen energy recovery during wastewater purification, providing a feasible path for "waste treatment and resource recovery."
[0074] 5. Degradation performance test of catalytic materials in continuous flow reaction
[0075] The catalyst obtained in Example 2 was tested in a continuous flow reactor.
[0076] Test method: A thin film of 10 mg of catalyst was deposited on a quartz plate and placed in a 250 mL beaker. A peristaltic pump was used to circulate 100 mL of 10 mg / L tetracycline solution in the beaker to create a flow environment. Degradation was then induced by light and ultrasound. Results are as follows: Figure 11 As shown.
[0077] Depend on Figure 11 The results showed that the material exhibited good degradation performance in 100 mL of 10 mg / L tetracycline aqueous solution in the Qinhuai River, Lanyue Lake, laboratory tap water, and deionized water. The degradation rates reached 71.71%, 64.88%, 67.06%, and 60.91% within the first 30 minutes of reaction, respectively, and the final degradation rates after 5 hours were 86.78%, 87.33%, 84.19%, and 95.37%, respectively. These results indicate that the catalyst retains efficient and stable piezoelectric-photocatalytic performance in a flowing system, demonstrating its potential for practical application.
[0078] 6. Stability testing of catalytic materials
[0079] The stability of the catalyst material in Example 2 was tested. The test method was as follows: After the reaction was completed, the catalyst was recovered by centrifugation, then washed with deionized water and ethanol, and dried overnight in a vacuum drying oven at 60 °C in preparation for the cycle stability test. The results are shown in Figure 12.
[0080] Depend on Figure 12 It was found that the degradation maintained good stability after 4 hours of TC degradation testing. The degradation efficiencies for the four cycles were 95.93%, 91.07%, 89.44%, and 88.42%, respectively.
Claims
1. A carbon nitride-based composite piezoelectric-photocatalytic material, characterized in that, The catalytic material is formed by depositing flower-shaped molybdenum disulfide nanoparticles on the surface of carbon nitride nanosheets, wherein the molybdenum disulfide is 2H molybdenum disulfide; the contact surface between the molybdenum disulfide and carbon nitride forms a type I heterojunction under photoexcitation only, and transforms into a type S heterojunction under piezoelectric-optic conditions.
2. The carbon nitride-based composite piezoelectric-photocatalytic material according to claim 1, characterized in that, The mass ratio of molybdenum disulfide to carbon nitride is 1:2 to 1:
10.
3. The carbon nitride-based composite piezoelectric-photocatalytic material according to claim 1, characterized in that, The thickness of the carbon nitride nanosheets is 5~72 nm.
4. The carbon nitride-based composite piezoelectric-photocatalytic material according to claim 1, characterized in that, The flower-shaped molybdenum disulfide nanoparticles have a particle size of 200~300 nm.
5. A method for preparing the carbon nitride-based composite piezoelectric-photocatalytic material according to any one of claims 1 to 4, characterized in that, Includes the following steps: Carbon nitride nanosheets and flower-shaped molybdenum disulfide nanoparticles were dispersed in a solvent, ultrasonically mixed to achieve uniformity, dried, and finally calcined to obtain the carbon nitride-based composite piezoelectric-photocatalytic material.
6. The method for preparing the carbon nitride-based composite piezoelectric-photocatalytic material according to claim 5, characterized in that, The calcination conditions are: calcination at 290~300℃ for 1~1.5 hours under an inert gas atmosphere.
7. The method for preparing the carbon nitride-based composite piezoelectric-photocatalytic material according to claim 5, characterized in that, The solvent is ethanol.
8. The application of the carbon nitride-based composite piezoelectric-photocatalytic material according to any one of claims 1 to 4 in the degradation of organic pollutants and / or the generation of hydrogen.
9. The application according to claim 8, wherein the application is carried out under the synergistic conditions of mechanical vibration and light irradiation; the mechanical vibration is provided by ultrasound at a frequency of 20-50 kHz; and the light irradiation is full-spectrum.
10. In the application according to claim 8, the organic pollutant is tetracycline.